Nature's imagination : the frontiers of scientific vision - Cornwell, John, 1940- (Oxford : Oxford University Press, 1995)
"A person is not explainable in molecular, field-theoretical, or physiological terms alone." With that declaration, Nobel laureate Gerald M. Edelman goes straight to the heart of Nature's Imagination, a vibrant and important collection of essays by some of the world's foremost scientists. Ever since the Enlightenment, the authors write, science has pursued reductionism: the idea that the whole can be understood by examining and explaining each of its parts. But as this book shows, scientists in every discipline are reaching for a new paradigm that accounts for the whole - from the individual person to the universe itself. Nature's Imagination gathers together the work of thirteen leading mathematicians, astronomers, neuroscientists, and philosophers, as they discuss the revolution sweeping the sciences. Here Roger Penrose, Oliver Sacks, John Barrow, Gregory Chaitin, Maragret Boden, and others explore how and why classic reductionism is falling by the wayside in their own fields. As Freeman Dyson writes in the introduction, science is an art form, not a philosophical method, and it is always in search of new tools. Reductionism has done its work, and scientists are in search of another. Roger Penrose offers a fascinating account of irreducibility in mathematics, starting with the example of an impossible triangle - a drawing of a triangular object twisted so that could not exist in three dimensions. He breaks the triangle into three parts, showing that each corner is physically possible; only in combination is the triangle impossible. Both Penrose and mathematician Gregory Chaitin explore Godel's incompleteness theorem - as does John Barrow, who explains that Chaitin's proof of the theorem shows that, if we ever arrive at a Theory of Everything, there may be a still deeper and simpler unifying theory beyond that. Other contributors discuss the changing thinking in neuroscience, and the limitations of a mechanical view of the mind: as Oliver Sacks writes, "if we are to have a model or theory of mind as this actually occurs in living creatures in the world, it may have to be radically different from anything like a computational one." In addition, this volume includes staunch defenders of the classic scientific approach, such as Peter Atkins ("The omnicompetence of science, and in particular the simplicity its reductionist insight reveals, should be accepted as a working hypothesis until, if ever, it is proved inadequate"). The advance of science has been so startlingly swift in the last century that it has begun to approach limits never dreamed of before. This remarkable volume captures the latest thinking on where we must turn if we are to truly understand ourselves and the universe we live in.
Introduction. The scientist as rebel / F. Dyson -- Must mathematical physics be reductionist? / R. Penrose -- Randomness in arithmetic and the decline and fall of reductionism in pure mathematics / G.J. Chaitin -- Theories of everything / J.D. Barrow -- Intertheoretic reduction: a neuroscientist's field guide / P.M. Churchland and P.S. Churchland -- Neural Darwinism: the brain as a selectional system / G.M. Edelman and G. Tononi -- A new vision of the mind / O. Sacks -- The limitless power of science / P.W. Atkins -- Reductive megalomania / M. Midgley -- Artificial intelligence and human dignity / M.A. Boden -- On 'computabilism' and physicalism: some subproblems / H. Wang -- Knowledge representation and myth / W.F. Clocksin -- Memory and the individual soul: against silly reductionism / G.M. Edelman
Includes bibliographical references and index.
Keywords: Reductionism; Science -- Philosophy